(3OjhGf GHf SfGf GdNaGLjs - (3YHO Gddg Hf eMeO Hf SYjO Hf SfGf, CHh eMeO GdNaGLj GdMdHj,J (B466 (3g` s
(3ChdgG (B:s
(3bGd jeOM GdCLd fGUQ GdOhdI GHf MeOGf(B: (3GdSja efJbe hGdLO eYJPQ heG Ydjc EPG de jSYO GdbOQ s
(3BNQgG (B:s
(3djJ TYQj HCj TF COGQc abO bd aj QVGc EMJjGdj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B120s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B122 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B788s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs